2020
DOI: 10.1002/elps.201900462
|View full text |Cite
|
Sign up to set email alerts
|

Lactate determination in human vitreous humour by capillary electrophoresis and time of death investigation

Abstract: Forensic inquests, particularly, in assessing time since death currently recognize the importance of the analysis of vitreous humour (VH) biomarkers. Present research, studies, and validates the determination of lactate (La) in VH by CZE with indirect UV detection. The BGE (pH 8.9) consisted of Tris buffer (37 mM) containing 4‐methoxybenzoic acid (4 mM) and alkyl‐trimethyl‐ammonium bromide (1.2 mM). Each VH specimen was diluted with a butyric acid solution (internal standard 0.057 mM) and La and butyrate were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The regression equation was found to be y = 6.6033 x + 112.74. There were no other studies done in synovial fluid lactate levels for estimating time since death to compare our results, but a similar statistically significant positive correlation was obtained with the vitreous lactate levels in a study done by Bertaso et al 12 in 2020, with R 2 = 0.5268, P < 0.05, with regression equation of y = 0.1682 x + 20.29.…”
Section: Discussionsupporting
confidence: 82%
“…The regression equation was found to be y = 6.6033 x + 112.74. There were no other studies done in synovial fluid lactate levels for estimating time since death to compare our results, but a similar statistically significant positive correlation was obtained with the vitreous lactate levels in a study done by Bertaso et al 12 in 2020, with R 2 = 0.5268, P < 0.05, with regression equation of y = 0.1682 x + 20.29.…”
Section: Discussionsupporting
confidence: 82%
“…Lactate has been determined in biological samples mostly using enzymatic-and nonenzymatic-based sensors [12,[14][15][16][17][18]. However, other methods, such as CE [19][20][21][22], HPLC [23], and spectroscopy [24,25], can also be used. The determination of lactate in sweat has recently been extensively explored using colorimetric [26][27][28][29] and wearable electrochemical sensors [6,8,17,18,30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CE consumes small amounts of samples and reagents and generates low volumes of waste, making it environmental friendly. Therefore, several studies can be found in the literature regarding lactate determination by CE in various samples, particularly in biological matrices such as vitreous humor [19], exhaled breath condensate [22], plasma [21], and blood [20]. The application of CE for sweat analysis has also been explored [31][32][33][34][35][36][37][38][39][40], particularly for chloride determination aiming to diagnose cystic fibrosis [31-33, 35, 31, 38].…”
Section: Introductionmentioning
confidence: 99%